Qualitative Thematic Analysis of Transcripts in Social Change Research: Reflections on Common Misconceptions and Recommendations for Reporting Results - Kogen, Lauren (International journal of qualitative methods, 2024)
This paper, on qualitative thematic analysis (QTA) in social change research, falls somewhere between a reflective piece and a how-to guide. Using two examples from my own previous research, I discuss why QTA in the field of social change or social justice, which often analyzes the words of vulnerable, marginalized, or underserved populations, is so fraught, so contested, and so often dismissed. Qualitative thematic analysis of interviews or focus groups is a common research tool used in the field, but the guidelines, scope, and practices of this tool are varied and ill-defined. I have witnessed in my students’ papers and in peer reviewing for journals that there are a handful of assumptions and misconceptions that appear repeatedly, for example around intercoder reliability and frequency counting, that reduce the quality of analysis. This paper focuses on how to conduct QTAs that address social change: complex social problems faced by underserved populations, such as those dealing with poverty and inequality. By discussing the methods used in two of my own social change research projects, this paper offers a balanced method for both promoting rigor and understanding the limits and strengths of this method.